2007
DOI: 10.1007/s11199-007-9272-7
|View full text |Cite
|
Sign up to set email alerts
|

Feminism: What is it Good For? Feminine Norms and Objectification as the Link between Feminist Identity and Clinically Relevant Outcomes

Abstract: The goal of this study was to explore the relationships between feminism and clinical outcomes, such as eating attitudes, depression, and self-esteem, employing structural equation modeling to look at indirect relationships. This study examined female participants' (N=282) responses to an online survey measuring feminist self-identification, conformity to feminine norms, objectified body consciousness, eating attitudes, depression, and self-esteem. Participants were recruited on two college campuses and throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 35 publications
6
63
2
Order By: Relevance
“…For example, at the individual level of analysis, holding strong feminist beliefs has been linked with high self-esteem (Fischer and Good 1994), self-efficacy (Eisele and Stake 2008), academic achievement (Valenzuela 1993), rejection of feminine norms for thinness and appearance (Hurt et al 2007), sexual well-being (Schick et al 2008), and sexual openness (Bay-Cheng and Zucker 2007). At the level of interpersonal relationships, although some women continue to equate feminism with heterosexual disharmony (Rudman and Fairchild 2007), this stereotype is debunked by survey findings from men with feminist women partners who rate their relationship as both stable and sexually satisfying (Rudman and Phelan 2007).…”
Section: Feminist Beliefsmentioning
confidence: 99%
“…For example, at the individual level of analysis, holding strong feminist beliefs has been linked with high self-esteem (Fischer and Good 1994), self-efficacy (Eisele and Stake 2008), academic achievement (Valenzuela 1993), rejection of feminine norms for thinness and appearance (Hurt et al 2007), sexual well-being (Schick et al 2008), and sexual openness (Bay-Cheng and Zucker 2007). At the level of interpersonal relationships, although some women continue to equate feminism with heterosexual disharmony (Rudman and Fairchild 2007), this stereotype is debunked by survey findings from men with feminist women partners who rate their relationship as both stable and sexually satisfying (Rudman and Phelan 2007).…”
Section: Feminist Beliefsmentioning
confidence: 99%
“…The instrument has been used to examine its relationships with eating disorders and other clinical outcomes (Green, Davids, Skaggs, Riopel, & Hallengren, 2008;Hurt et al, 2007;Mahalik et al, 2005).…”
Section: Drafting the Original Questionnaire On The American Populationmentioning
confidence: 99%
“…Benevolent sexism is a sexist view that women need additional help with certain activities, for instance carrying items, because of their gender (Glick and Fiske 1996). Previous research has shown both of these phenomena to have negative consequences for women (Dardenne et al 2007;Fredrickson et al 1998;Hurt et al 2007;Noll and Fredrickson 1998;Roberts 2004;Sibley and Wilson 2004). Previous research suggests that one outcome of benevolent sexism is to encourage women to adhere to their proscribed gender roles (Glick and Fiske 2001).…”
Section: Introductionmentioning
confidence: 99%